From the methodology of using nonstandard tests in the design of practical training on number theory (Eurasian Scientific Herald, 2023)
This article discusses the development of numbers, the extension of number systems, and the concepts underlying the notions of integers, rational and complex numbers. Recommendations are given for the effective implementation of all numerical extensions and their characteristics, using non-standard tests.